𝙏𝙚𝙧𝙢𝙞𝙣𝙖𝙡𝙞𝙖 𝙘𝙝𝙚𝙗𝙪𝙡𝙖 Extract Inhibited Biofilm Formation and Enhanced Antibacterial Activity of Antibiotics against some Drug Resistant Bacteria - Kongchareonsuntorn, Wisatre; Yengprakhon, Natthanika (Burapha Science Journal, 2024)
Background and Objectives : Terminalia chebula is commonly used to treat frequent disease. This study investigated the synergistic effect of an ethanol extract from Terminalia chebula fruit in combination with antibiotics against some bacteria. Methodology : Antimicrobial activity was determined by Broth microdilution susceptibility test, Synergy effect of Terminalia chebula extract in combination with antibiotics was tested by Checkerboard assay and antibiofilm activity was conducted by Crystal violet staining assay. Main Results : T. chebula extract combined with Ampicillin had synergistic effect against B. cereus and B. subtilis by the FICI values of 0.187 and 0.14, respectively. Likewise, the synergism of T. chebula extract combined with Oxytetracycline was detected against E. coli and FICI value was 0.5. The antibiofilm activities of T. chebula extract were examined and the results showed that T. chebula extract inhibited the biofilm formation of E. coli, P. aeruginosa, and S. aureus during 8–24 hours of incubation. Oxytetracycline inhibited the biofilm formation of E. coli, P. aeruginosa and S. aureus better than T. chebula extract at 4–12 hours. Conclusions : An ethanol extract from Terminalia chebula fruit showed synergy effect with ampicillin and oxytetracycline and had antibiofilm activity against some bacteria.